The birth of doubt confronting uncertainty in early rabbinic literature - Halberṭal, Mosheh 1958-; Fischer, Elli (Providence, Rhode Island Brown Judaic Studies, 2020)
"In the rabbinic laws in the Mishnah, the Sages constructed an entire field of instructions concerning how to behave in situations of uncertainty ranging from matters of ritual purity, to lineage and marriage, to monetary law, and to the laws of forbidden foods. Reflecting on the weight assigned to different possible errors that could be made and examining the norms of uncertainty opens a window for understanding the early rabbinic that reflected rules aimed not at avoidance but rather at dwelling in the midst of uncertainty, thus rejecting sectarian isolationism meant to minimize a community's friction with uncertainty"--
"In the history of halakhah, the treatment of uncertainty became one of the most complex fields of intense study. In his latest book, Moshe Halbertal focuses on examining the point of origin of the study of uncertainty in early rabbinic literature. Halbertal explores instructions concerning how to behave in situations of uncertainty ranging from matters of ritual purity, to lineage and marriage, to monetary law, and to the laws of forbidden foods in the Mishnah, Tosefta, and halakhic midrashim. This examination of the rules of uncertainty introduced in early rabbinic literature reveals that these rules were not aimed at avoiding but rather at dwelling in the midst of uncertainty, thus rejecting the sectarian isolationism that sought to minimize a community’s experience of and friction with uncertainty."--Page 4 of printed paper wrapper
Includes bibliographical references and indexes
Keywords: Rabbinical literature -- History and criticism; Uncertainty; Uncertainty -- Religious aspects; Jewish Law -- Interpretation and construction; Judaism -- History -- Talmudic period, 10-425; Jewish law ; Interpretation and construction; Judaism ; Talmudic period; Rabbinical literature; Uncertainty ; Religious aspects; Criticism, interpretation, etc; History